N2-fixing bacteria are more sensitive to microtopography than nitrogen addition in degraded grassland - Li, Chengyi; Valencia, Enrique; Shi, Yan; Zhou, Guiyao; Li, Xilai (Frontiers in Microbiology, 2023)
Soil bacteria play a crucial role in the terrestrial nitrogen (N) cycle by fixing atmospheric N2, and this process is influenced by both biotic and abiotic factors. The diversity of N2-fixing bacteria (NFB) directly reflects the efficiency of soil N fixation, and the diversity of NFB in degraded alpine meadow soil may change with different N fertilizing levels and varied slopes. However, how N addition affects the diversity of NFB in degraded alpine meadows, and whether this influence varies with slope, remain poorly understood. To address this deficiency, we conducted an N addition field experiment at three levels (2, 5, and 10 g N•m -2 •a -1 ) to study the effects of N addition on soil NFB diversity on two different slopes in a degraded meadow on the Tibetan Plateau. Our results showed that there were significant differences in the dominant bacterial species between the two slopes. The Chao1 index, species richness, and beta diversity of NFB did not differ significantly between slopes, but the Shannon index did. Interestingly, N addition had no effect on the diversity of NFB or the abundance of dominant bacteria. However, we did observe a significant change in some low-abundance NFB. The community composition and diversity of NFB were significantly positively correlated with slope and soil physicochemical properties (e.g., total potassium, pH, and total nitrogen). Overall, our study highlights the variation in NFB communities among different slopes in degraded alpine meadows and their resilience to exogenous N addition. Our results also underscore the importance of considering the effects of micro-topography on soil microbial communities in future studies of alpine ecosystems.